Managing Weedy Biotic Stress in Linseed (Linum usitatissimum L.) for Enhanced Production: A Comprehensive Review - Acharya, Shivasankar; Nirala, R. B. P.; Vishwakarma, Ramanuj; Singh, Anil Kumar; Ghosh, Mainak; Chowdhury, Arnab Roy (International Journal of Economic Plants, 2024)
Linseed is an oldest oilseed crops having multiplicity of uses, grown for yielding oil as well as fibre. Among the various biotic factors affecting linseed productivity, weeds are regarded as most disdain to crop production, because of the initial slow growth and relatively lower canopy spread, resulting in non-realization of desired level of productivity of the crop. Weed dynamics in linseed depends on agro-climatic situation, soil characteristics, cropping pattern, crop management practices and availability of soil moisture in the field. Manual weeding is labour intensive and is comparatively more time consuming, which necessitates a cost-effective chemical weed management practice for controlling weeds. Combination of pre-emergence herbicides followed by post-emergence herbicides provides an effective weed management since the pre-emergence herbicides does not allow the emergence of most of weeds through their action in inhibiting root and shoot growth, whereas, post-emergence application controls effectively the weed flush which germinates after getting the first irrigation. This article critically reviews the crop-weed competition, weed dynamics and their impact on linseed yield, including various research efforts taken by researchers in controlling the weeds. As very less research work is being conducted in India by various Agricultural Universities on weed management aspects of linseed, the future challenge should focus research on major areas of weed ecology, assessment of on-farm losses caused by weeds, bio-efficacy of post-emergence herbicides and on-farm assessment of available integrated weed management options in linseed for sustainable linseed production.